2012
DOI: 10.4081/oncol.2012.208
|View full text |Cite
|
Sign up to set email alerts
|

Role of viruses in oral squamous cell carcinoma

Abstract: The etiology of oral squamous cell carcinoma (OSCC) is complex and involves many factors. The most clearly defined risk factors are smoking and alcohol, which substantially increase the risk of oral SCC. However, despite this clear association, a substantial proportion of patients develop OSCC without exposure to them, emphasizing the role of other risk factors such as genetic susceptibility and oncogenic viruses. Some viruses are strongly associated with OSCC while the association of others is less frequent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Despite the fact that oral transmission of HPV is unclear, different sexual habits, such as the onset of sexual activity at an earlier age, an increase in the number of partners, and orogenital sex have made HPV an endemic infection [2]. As a result, some studies have shown the role of viruses in head and neck cancer [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that oral transmission of HPV is unclear, different sexual habits, such as the onset of sexual activity at an earlier age, an increase in the number of partners, and orogenital sex have made HPV an endemic infection [2]. As a result, some studies have shown the role of viruses in head and neck cancer [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is the sixth most common cancer originating from squamous cells of oral cavity, resulting in high annual morbidity and mortality worldwide. OSCC is a subtype of head and neck cancer that contributes up to 90% of total head and neck cancer .…”
Section: Introductionmentioning
confidence: 99%
“…The role of herpes simplex virus 1 in the occurrence of SCC is not yet clearly elucidated in literature. However, hypotheses suggest that Herpes Simplex Virus (HSV) infection would promote a state of chronic inflammation responsible for the malignant degeneration of cells, and also that the transient acquisition of a complete or incomplete viral genome can be sufficient to induce malignant transformation of host cells in vivo, resulting in the development of neoplastic cells [8]. The vesicular and ulcerative aspect of the lesion is the most commonly form found in literature and thus represents the most severe aspect found in HIV-positive patients [2,9].…”
Section: Discussionmentioning
confidence: 99%